Determination of pKa of ammonium and phenolic groups: Evidence of intramolecular hydrogen bonding in aqueous solution - Ariffin, Azhar; Khan, Mohammad Niyaz; Sim, Y.L.; Ahmad, W.H.W. (2008)
The ionization constants of 2-hydroxyanilinium, 2-methoxyanilinium, 4-nitroanilinium ions, N-(2′-hydroxyphenyl)-phthalamic acid and N-(2′-methoxyphenyl) phthalamic acid, determined spectrophotometrically, have been rationalized in terms of internal hydrogen bonding and steric hindrance between o-substituent and reaction site.